Trastuzumab administration during pregnancy: A systematic review and meta-analysis - Zagouri, F.; Sergentanis, T.N.; Chrysikos, D.; Papadimitriou, C.A.; Dimopoulos, M.-A.; Bartsch, R. (Breast Cancer Research and Treatment, 2013)
Landmark studies have established trastuzumab in the treatment of HER2-positive breast cancer. The present systematic review and meta-analysis aims to synthesize all available data, so as to evaluate the safety of trastuzumab during pregnancy. This study was performed in accordance with the PRISMA guidelines. All studies that examined the safety of trastuzumab administered during pregnancy, regardless of sample size, were considered eligible. Overall, 17 studies (18 pregnancies; 19 newborns) were included. In 55.6 % of cases, trastuzumab was administered in the metastatic setting. The mean duration of trastuzumab administration was 14.8 weeks. Occurrence of oligohydramnios/anhydramnios (O/A) was the most common (61.1 %) adverse event. 73.3 % of pregnancies exposed to trastuzumab during the second/third trimester were complicated with O/A; the respective rate of pregnancies exposed to trastuzumab exclusively during the first trimester was 0 % (P = 0.043). The mean GA at delivery was 33.8 weeks, and the mean weight of babies at delivery was 2,261 gr. In 52.6 % of cases, a healthy neonate was born. At the long-term evaluation, all children without problems at birth were healthy with a median follow-up of 9 months, while four out of nine children facing troubles at birth were dead within an interval ranging between birth and 5.25 months. All children exposed to trastuzumab in utero exclusively in the first trimester were completely healthy at birth. Trastuzumab should not be administered during pregnancy. However, for women who become accidentally pregnant during trastuzumab administration and wish to continue pregnancy, trastuzumab should be stopped and pregnancy could be allowed to continue. © 2012 Springer Science+Business Media New York.
Keywords: breast cancer; Oligohydramnios; Pregnancy; Trastuzumab